Apparent synonymous mutation F9 c.87A>G causes secretion failure by in-frame mutation with aberrant splicing. Issue 179 (July 2019) - Odaira, Koya; Tamura, Shogo; Suzuki, Nobuaki; Kakihara, Misaki; Hattori, Yuna; Tokoro, Mahiru; Suzuki, Sachiko; Takagi, Akira; Katsumi, Akira; Hayakawa, Fumihiko; Okamoto, Shuichi; Suzuki, Atsuo; et al.
Abstract: Introduction: Hemophilia B is an X-linked recessive bleeding disorder caused by coagulation factor IX (FIX) gene ( F9 ) mutations. Several F9 synonymous mutations have been known to cause hemophilia B; however, the deleterious mechanisms underlying the development of hemophilia B have not been completely understood. To elucidate the molecular pathogenesis causing hemophilia B, we investigated the synonymous F9 mutation: c.87A>G, p.(Thr29=). Materials and methods: The influence of F9 c.87A>G on mRNA splicing was analyzed by exon-trap assay and in silico prediction. We prepared FIX expression vectors using mutant F9 cDNA and transfected HepG2 cells to investigate intracellular transport and extracellular secretion of FIX. Intracellular kinetics of the expressed FIX was examined by treatment with the proteasome inhibitor MG132. Results: Exon-trap analysis revealed that F9 c.87A>G resulted in almost (99.1%) aberrant splicing (r.83_88del). In silico analysis predicted that F9 c.87A>G influenced the splicing pattern by generating an available aberrant 5′ splice site. The aberrant F9 mRNA (r.83_88del) was translated to a mutant FIX p.Cys28_Val30delinsPhe with an in-frame mutation at the signal peptide cleavage site. Simultaneously, a small amount (0.9%) of mutant F9 r.87A>G translating into WT FIX p.Thr29 = was also observed. The mutant FIX was abnormally retained in the endoplasmic reticulum (ER) and was not extracellularly secreted. It appeared to be intracellularly degraded via proteasome-dependent degradation machinery. Conclusion: F9 c.87A>G was found to cause abnormal mRNA splicing, r.83_88del, and produce the mutant FIX p.Cys28_Val30delinsPhe. The mutant FIX is an abnormal protein with extracellular secretory defects and is intracellularly eliminated via proteasome-dependent ER-associated degradation. Highlights: F9 c.87A>G caused an abnormal splicing pattern via aberrant 5′ss, F9 r.83_88del. F9 r.83_88del appeared to be translated into FIX p.Cys28_Val30delinsPhe. FIX p.Cys28_Val30delinsPhe was an in-frame mutant at signal peptide cleavage site. The in-frame mutant FIX was abnormally retained in endoplasmic reticulum. The retained mutant FIX was eliminated via a proteasome-dependent system.